Relevansi Kegiatan Khitobah terhadap Kemampuan Public Speaking Peserta Didik di MAN 2 Karanganyar - Ridho, Ahmad Rasyid; Hasanah, Amalia; Sugiyarti, Sri; Ahmadi, Fauzan; Saifudin, MH. (Asian Journal of Islamic Studies and Da'wah, 2024)
One of MAN 2 Karanganyar's efforts in helping students improve students' public speaking skills can be done at school through various forms of activities, one of which is speech or khitobah activities. This paper describes the relevance of khitobah activities to students' public speaking skills at MAN 2 Karanganyar. The purpose of this paper is to describe the khitobah activities at MAN 2 Karanganyar, the obstacles experienced and the supporting factors and their relevance to the public speaking skills of MAN 2 Karanganyar students. The data sources of this research are rohis members, students who have served and supervising teachers. The research methods used in this research are interviews and direct observation. The results of this study indicate that the positive impact felt by students who berkhitobah is their public speaking skills are increasing, namely their religious knowledge is increasing because students also indirectly while learning religion through khitobah dzuhur activities. Learners also learn to understand how the method and how to give a good speech or khitobah.